PERANAN CLINICAL GOVERNANCE TERHADAP PENJAMINAN MUTU RUMAH SAKIT : Sistematik Review - Adhar Arifuddin; Siti Rochmiyati; A Fahira Nur; Nur Eka Dyastuti; Hidayanti Arifuddin; Vidyanto (Universitas Tadulako, 2022)
This study is a systematic review to obtain an overview of previous studies regarding the role of clinical governance in hospital quality assurance. Article searches were conducted on academic search complete, medline with full text, Proquest and Pubmed, EBSCO, and Scinapse using selected keywords, namely: Clinical Governance, Hospital, Quality Assurance. A total of 70 journals from journals found according to the search keywords were then screened, and 10 full text journals were obtained that met the criteria for review. The search results from various articles as literature sources, found several roles of clinical governance on hospital quality assurance, namely as: Clinical audit, Preparation of Medical Service Standards, Nursing Indicators, Quality Management, Clinical Leadership/ Doctor Involvement, Clinical Effectiveness, Training and Education, Transparency, Accountability, Responsibility, Independence, Equality and Fairness, Systematic Implementation, Revalidation, Involving Staff and Patients in Quality Improvement, and Encouraging a Culture of Continuous Improvement. Research is needed on how big the contribution of clinical governance is to changes in the quality of health services. So that it can be arranged in the form of a clinical governance priority scale, and the division of roles in providing satisfactory health services to all parties, both patients, patient families, and stakeholders.